Administrative ironies and DHS performance reporting. Issue 1 (1st March 2017) - Herzog, Richard J.; Counts, Katie S.
Abstract : Objectivism is the critical lens used to view organizational communication of the U.S. Department of Homeland Security (DHS). The Government Performance Results Modernization Act of 2010 changed requirements for such communication by mandating that agencies like DHS emphasize performance goals and targets to be achieved in the upcoming years in their performance reporting. Interpretivism is the sense-making lens used to view changes in performance reporting. This study focuses on performance target reductions, new performance measures, and retired performance measures documented in a DHS annual report. Nineteen performance measures were selected and discussed from empirical interpretivist and institutional interpretivist lenses. When intepretivism cannot match what is reported with what would appear to be logical, administrative ironies are established.